Genetic Variability, Correlation, and Path Analysis of Thai Commercial Melon Varieties - Thanet Khomphet; Warin Intana; Athakorn Promwee; Shams Shaila Islam (International Journal of Agronomy, 2022)
In the selection phase of melon breeding programs, genetic variability is a critical component for yield improvement. The goals of this study were to discover the variables that affect melon fruit weight and examine genetic variability, correlation, and path analysis of eight melon varieties. The experiment was arranged as a completely randomized block design with 4 blocks. It was conducted between July and September 2021 at the School of Agricultural Technology, Walailak University, Nakhon Si Thammarat, Thailand. The result found that stem diameter and length, leaf length, width, number, and chlorophyll, day to 50% male and female flowering, and fruit perimeter, height, and weight were highly significant across the varieties. The genotypic coefficients of variation (GCV) of observed variables were all lower than phenotypic coefficients of variation (PCV). Fruit weight (15.462 and 19.865%) had the highest GCV and PCV. High broad-sense heritability was linked to high (H) or moderate (M) genetic advance as a percentage of the mean from stem length (67.606%: H and 21.992%: H), fruit weight (60.586%: H and 24.793%: H), fruit perimeter (76.395%: H and 12.258%: M), and fruit height (69.828%: H and 12.122%: M). The maximum and significant genotypic correlation value was obtained between leaf length and leaf width (r = 1.000). Fruit weight is positively correlated with fruit perimeter (r = 0.940) and fruit height (r = 0.831). According to correlation and path analyses, stem diameter and length, leaf chlorophyll, and fruit perimeter and height were considered variables for fruit weight improvement in the breeding programs. It suggests that the increase in traits with a favorable direct influence on fruit weight may directly contribute to fruit weight.